2019
DOI: 10.1016/j.ijcha.2019.100414
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary prevalence, trends, and outcomes of coronary chronic total occlusions in acute myocardial infarction with cardiogenic shock

Abstract: Background There are limited data on the prevalence and outcomes of chronic total occlusions (CTO) of the coronary artery in acute myocardial infarction with cardiogenic shock (AMI-CS) patients. Methods Using the National Inpatient Sample, all admissions with AMI-CS that underwent diagnostic angiography between January 1, 2008, and December 31, 2014, were included. CTO, percutaneous coronary intervention (PCI), comorbidities and concomitant cardiac arrest was identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…After adjusting for confounders, the presence of CTO was significantly associated with cardiac and all-cause mortality at 30-days and 5-years follow-ups. Consistent with these results, Vallabhajosyula et al demonstrated that the presence of CTO in patients with STEMI and cardiogenic shock was associated with increased in-hospital mortality [ 68 ]. Interestingly, the impact of the number of CTO on clinical outcome was also identified [ 69 ].…”
Section: Cto-pci In Patients With Amisupporting
confidence: 58%
“…After adjusting for confounders, the presence of CTO was significantly associated with cardiac and all-cause mortality at 30-days and 5-years follow-ups. Consistent with these results, Vallabhajosyula et al demonstrated that the presence of CTO in patients with STEMI and cardiogenic shock was associated with increased in-hospital mortality [ 68 ]. Interestingly, the impact of the number of CTO on clinical outcome was also identified [ 69 ].…”
Section: Cto-pci In Patients With Amisupporting
confidence: 58%
“…During the period between 1 January 2000 through 31 December 2016, a retrospective cohort of admissions from the HCUP-NIS with a primary diagnosis of AMI (International Classification of Disease-9 Clinical Modification [ICD-9CM] 410.x; International Classification of Disease-10 Clinical Modification [ICD-10CM] I21.x-22.x) receiving ECMO support (ICD-9CM 39.65; ICD-10CM 5A15223) were identified consistent with prior literature [7]. Deyo's modification of Charlson Comorbidity Index was used to identify co-morbid diseases and prior methodology was used to identify cardiac and non-cardiac procedures [2,3,7,8,11,[13][14][15][16][17][18][19][20][21][22][23]. We identified relevant complications and categorized them as (a) vascular complications-arterial injury, acquired arterio-venous fistula, and vascular complications requiring surgery; (b) lower limb amputation; (c) hematologic-post-operative hemorrhage, hemolytic anemia, thrombocytopenia, and blood transfusion; and (d) neurologic-ischemic or hemorrhagic stroke ( Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Demographic characteristics, hospital characteristics, acute organ failure, coronary angiography, percutaneous coronary interventions (PCI), and mechanical circulatory support (MCS) use were identified for all admissions using previously used methodologies from our group. [2][3][4][5]8,9,[28][29][30][31][32][33][34][35] Acute noncardiac organ failure was classified as respiratory (acute respiratory failure, other pulmonary insufficiency, acute respiratory distress syndrome, respiratory arrest, and ventilator management), renal (acute kidney injury), and hepatic (acute hepatic failure, hepatic encephalopathy, hepatic infection, and hepatitis unspecified), hematologic (defibrination syndrome, acquired coagulation factor deficiency, coagulation defect, and thrombocytopenia), and neurologic (anoxic brain injury, acute encephalopathy, coma, altered consciousness, and electroencephalogram). [3][4][5]9,30,32 Similar to prior literature from the HCUP-NIS, we used the procedure day for RHC/PAC placement to time concomitant coronary angiography, PCI, MCS, and invasive mechanical ventilation.…”
Section: Study Population Variables and Outcomesmentioning
confidence: 99%